The Effectiveness of Training Circuits in Volleyball Games - Hakim, Hikmad; Ishak, Muhammad; Bismar, Ahmad Rum (Journal of Sport Education, Coaching, and Health (JOCCA), 2023)
This study is a quantitative description study that aims to determine the effectiveness of circuit training in volleyball games. The method used was a quantitative survey with data collection techniques using agility, strength, and endurance tests. the subjects in this study were volleyball games of students at SMAN 3 Pinrang totaling 30 people. Data analysis techniques use quantitative descriptive analysis in the form of percentages and requirements tests. Based on the results of research and discussion, the results of the Training Circuit on volleyball in SMAN 3 Pinrang students were agility of 33.33%, strength of 33.33%, and endurance of 33.33%.